Meta Analysis of Factors Determining Postnatal Care Utilization - Astari, Rahmi Windhy; Wardani, Aulia Ayu Kusuma; Maryana, Dyan; Kurniati, Era; Murti, Bhisma; Tursina, Elsa (Journal of Maternal and Child Health, 2024)
Background: Maternal and infant morbidity and mortality continue to be a challenge today. Most maternal and newborn deaths occur during the early postnatal period. This condition can be caused by low utilization of postnatal care services. This study aims to analyze and estimate the influence of determining factors on the utilization of postnatal care services. Subjects and Method: Meta-analysis was conducted using PRISMA guidelines and PICO format. Population: Postpartum Mothers. Intervention: high antenatal care, high maternal education, high family income and delivery in hospital. Comparison: low antenatal care, low maternal education, low family income, home birth. Outcome: postnatal care services. Cross-sectional study articles were collected from Google Scholar, PubMed, and Science Direct databases. The search strategy used the keywords: "Determinant Postnatal Care" AND "Maternal Health Service" AND "Cross-Sectional". The inclusion criteria for this study were full-text, cross-sectional studies published from 2014 to 2023. Data from articles were extracted with RevMan 5.3. Results: The meta-analysis included 16 cross-sectional studies from Ethiopia, Ghana, Kenya, and Malawi. The total sample was 29,165 postpartum mothers. Postnatal mothers with high antenatal care visits (aOR= 2.64; 95% CI= 1.87 to 3.71; p = 0.001), high education (aOR= 2.09; 95% CI= 1.67 to 2.63; p = 0.001), high family income (aOR= 1.63; 95% CI= 1.25 to 2.11; p = 0.002), and hospital delivery (aOR= 1.58; 95% CI= 1.15 to 2.97; p = 0.010) allow the utilization of postnatal care services and these results were statistically significant. Conclusion: The results of this study reveal that high antenatal care, high maternal education, high family income and delivery in hospital have a positive effect on the utilization of postnatal care services.